Sekularitas Dan Spritualitas: Mencari Format Integrasi Ilmu Untuk Konstruksi Kurikulum Pendidikan Islam - Abdusima Nasution (JURNAL TARBIYAH, 2018)
One of the most desirable objectives of Islamic education is the realization of a harmonious civil society between faith, science and morals. Science without faith is blind, faith without science is paralysis, while the integration between faith and science will manifest in morals. In its operational level, as a guide to educational indicators, it is contained in a stage called the curriculum. Achievements and successes of education are also determined by the curriculum. Building a framework of Islamic education curriculum quality ideally combines rational and soul which in term is known as secularity and spirituality. With these two principles will fill the science and faith later. Therefore, the Prophet SAW hinted for the goodness in the world and life hereafter is knowledge.  The integration between knowledge and religious knowledge should be covered in curriculum.